A new color image encryption scheme based on 2DNLCML system and genetic operations. (May 2020) - Zhang, Ying-Qian; He, Yi; Li, Pi; Wang, Xing-Yuan
Highlights: A new color image encryption scheme is proposed based on the spatiotemporal chaos of the two dimensional nonlinear coupled map lattices (2DNLCML) and genetic operations. Due to the spatial nonlinear coupling, this 2DNLCML system can generate superior pseudo-random sequences for image encryption. The scheme employs genetic operations followed by mutation and crossover operation using binary encoding, which consumes a low amount of computational cost. Simulation results indicate that the proposed scheme has a good encryption effect and can resist various typical attacks. Abstract: Based on the spatiotemporal chaos of the two Dimensional Nonlinear Coupled Map Lattices (2DNLCML) and genetic operations, a new optical color image encryption scheme is proposed. Because of the spatial nonlinear coupling which replaces traditional adjacent coupling, the 2DNLCML system contains good features such as ergodic pseudo-random sequence, less periodic windows in bifurcations and larger range of parameters in chaotic dynamics, which is more suitable for image encryption. The scheme also performs genetic operations including mutation and crossover for binary coding, thus reducing the computational complexity. Simulations have been carried out and the results demonstrate that the proposed algorithm has properties of large key space, high sensitivity to key, strong resisting attack. So, it is more secure and effective algorithm for encryption of digital images.